Pattern of exposure among victims of suspected rabid animal attending anti-rabies clinic of tertiary care hospital - Qureshi, Uruj A.; Qureshi, Mariya A. (International Journal Of Community Medicine And Public Health, 2018)
Background: Rabies, a neglected tropical disease, is vaccine preventable and occurs in more than 150 countries. It is almost always fatal. About 40% of deaths due to rabies occur in children under the age of 15 years. Objectives were to study the pattern of injury following exposure to canine bite, bear maul and rabid cow among the attendees of Antirabies clinic of SMHS hospital, Srinagar and to classify the type of exposure using WHO guidelines for initiation of post exposure prophylaxis. Methods: The study was conducted over a period of three months from 1st June 2016 to 31st August 2016, in Anti Rabies Clinic of Department of Community Medicine, Government Medical College, Srinagar. It was a descriptive Study and included all victims of canine bite and rabid cow. A total of 134 patients were received. Results: Most [83 (61.9%)] of the patients were males with mean age of 36.63 years. Legs were the most common [57 (43.2%)] site of exposure followed by hands [15 (11.2%)] and thigh [13 (9.7%)]. Contact with a rabid cow was present in 5 (3.7%). Class II exposure was most frequently encountered [83 (61.9%)]. Class III exposure was seen in 49 (36.6%). All patients who attended anti rabies clinic for post exposure prophylaxis received free Antirabies Vaccine. Combined Antirabies vaccine and immunoglobulin was received by 49 (36.6%). Conclusions: Dog bite related injuries happen frequently in Srinagar. There is proper post exposure prophylaxis in place in SMHS hospital. There is need for curbing the ever increasing dog population and enforcing rabies vaccination in dogs.